ANALISIS TRANSFER RATE WIRELESS LOCAL AREA NETWORK DENGAN STANDAR IEEE 802.11A DAN IEEE 802.11G PADA KANAL LINE OF SIGHT - F Ammar; Hanafi Hanafi (Jurusan Teknik Elektro, Universitas Bangka Belitung, 2016)
WiFi works on the 2.4 GHz band and 5 GHz. WiFi standard that works at this frequency, among others IEEE802.11g and IEEE802.11a. In this study measured the download and upload transfer rate of data with standard IEEE802.11g and IEEE802.11a. Measurements carried out on the canal Line of Sight (LOS), using two laptops to connected with the Access Point (AP) standard IEEE802.11g and IEEE802.11a. The results were obtained, the IEEE802.11g standard, download and upload transfer rate highest data 2.662,54.KB / s and 2549.60 KB / s, and the lowest 484,50.KB / s and 477.40 KB / s, while the IEEE802.11a standard, the transfer rate of the highest data download and upload 8104.68 KB / s and 5744.24 KB / s, and the lowest was 872.24 KB / s and 465,38.KB / s. In IEEE802.11g standard, the transfer rate of download and upload data at the lowest signal to below 35% and 30%, of the transfer rate of data downloads and uploads the highest. In the IEEE802.11a standard, the transfer rate of download and upload data at the lowest signal quality to below 20% and 30%, of the transfer rate of data downloads and uploads the highest. Data download transfer rate capability Standard IEEE802.11a, 2-3 times better at the highest signal quality condition, and no more than 2 times the lowest signal quality condition, compared the ability of downloading data transfer rate standard IEEE802.11g. The ability of data transfer upload rate IEEE802.11a Standard, 1.4 to 3 times better in the conditions of the highest quality signal, and 1-3 times better at low signal quality conditions, than the ability to upload the data transfer rate standard IEEE802.11g.